The Effects of Environmental, Social, and Governance (ESG) Disclosure Score on the Financial Performance of Energy and Mining Companies in Indonesia (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on the financial performance of companies in the energy and mining sectors in Indonesia. The research employs a quantitative method using multiple linear regression to examine the influence of the ESG pillars Envi-ronmental, Social, and Governance both individually and collectively on Return on Assets (ROA) and Return on Equity (ROE). The results indicate that overall ESG Pillar disclosure has a positive coefficient but does not have a statistically significant effect on corporate financial performance. The Social pillar shows a significant effect in improving ROE, while the Environmental and Governance pillars, despite having positive and negative coefficients respectively, do not exhibit statistically significant impacts on company profitability. This study highlights the importance of ESG integration particularly the Social aspect into the business strategies of energy and mining companies in Indonesia to enhance competi-tiveness, sustainability, and investor trust.